EMPOWERMENT OF FARMER GROUPS THROUGH INNOVATION OF NATURAL PLANT GROWTH REGULATORS FROM BAMBOO SHOOTS IN COT CUT VILLAGE, ACEH BESAR: PEMBERDAYAAN KELOMPOK TANI DENGAN INOVASI ZPT ALAMI REBUNG BAMBU DI DESA COT CUT ACEH BESAR - Oktarisa Nurul Mukminin; Mulyanti; Dewi Yana; Lukman Martunis; Mizar Liyanda; Yusran Akbar; Magfirah; Sri Agustina; Ika Rezvani Aprita; Chairil Anwar; Endiyani; Irhami; Nurhatijah; Humeira; Kurnia; Masyitah; Zulvia Maika Letis; Mulla Kemalawaty; Hayatun Nufus (PT. ROCE WISDOM ACEH, 2026)
Plant Growth Regulators (PGRs) are organic compounds that are not classified as plant nutrients but are biologically active at low concentrations and can stimulate, inhibit, or modify plant growth and development. The objective of this community service program was to develop a fermentation technique for bamboo shoots into a PGR solution and to enhance farmers’ capacity through extension services and hands-on training. This program was implemented by lecturers and students of Politeknik Indonesia Venezuela in Cot Cut Village, Kutabaro Sub-district, Aceh Besar Regency. The activities included field observation and the fermentation of bamboo shoots to produce PGRs. The fermentation process successfully yielded a dark-colored PGR solution with a characteristic aroma. The local community of Cot Cut Village showed strong enthusiasm for this program because it used natural materials that are inexpensive, readily available, and environmentally friendly. This activity demonstrates that bamboo shoots have significant potential as a source of natural PGRs and can serve as an innovative component of environmentally sustainable agriculture. Through this approach, bamboo shoots are expected to provide a simple yet impactful solution in supporting sustainable, locally based agricultural practices in Cot Cut Village, Kutabaro Sub-district, Aceh Besar Regency.